Hyper-connected generation and Discernment: A Franciscan perspective - Carbajo Núñez, Martín (Revista Eclesiástica Brasileira, 2019)
This article asserts the urgent need of discernment in our hyper-connected and hyper-accelerated society that drives people to frenetic activity and constant hurry. Furthermore, “the speed with which information is communicated exceeds our capacity for reflection and judgement.” The first part of the article focuses on discernment and indicates some of its characteristics, paying special attention to the Franciscan perspective. The second part reflects on how to practice it in order to meet the ethical challenges of our digital culture. Keywords: Discernment; Digital culture; Communication; Franciscanism; Ethics. Síntese: Este artigo afirma a urgente necessidade de discernimento em nossa sociedade hiperconectada e hiper-acelerada que leva as pessoas a ativismo frenético e constante pressa; além disso, “a velocidade da informação e da comunicada ultrapassa nossa capacidade de reflexão e julgamento”. Diante disso, a primeira parte do artigo concentra-se no discernimento e indica algumas de suas características, prestando especial atenção à perspectiva franciscana. A segunda parte reflete sobre como exercitar o referido discernimento ante os desafios éticos de nossa cultura digital.